Certain Class of Analytic Functions with respect to Symmetric Points Defined by Q-Calculus. (26th August 2021) - Karthikeyan, K. R.; Murugusundaramoorthy, G.; Purohit, S. D.; Suthar, D. L.
Abstract : In this study, we familiarise a novel class of Janowski-type star-like functions of complex order with regard to j, k -symmetric points based on quantum calculus by subordinating with pedal-shaped regions. We found integral representation theorem and conditions for starlikeness. Furthermore, with regard to j, k -symmetric points, we successfully obtained the coefficient bounds for functions in the newly specified class. We also quantified few applications as special cases which are new (or known).